SEMIOTIKA NARATIF GREIMASIAN DALAM IKLAN BUSANA MUSLIM - Nasrullah, Rulli (Sekolah Pascasarjana UGM, 2013)
Muslim Fashion has transformed to be cultural industry profitable financially. The flourish of Muslimfashion producers certainly needs business strategy to promote the products. Advertisement becomesone of promotional tools that can communicate product excellence. Moreover advertisement in massmedia gives space for producer to visualize image of product wanted especially when the advertisementis promoted in Muslim mass media. In semiotic tradition, advertisement does not only communicateproduct for sale but it has ideology constructed by both advertiser and advertising company in order toestablish in consumersâ thought including Muslim fashion that is no longer clothes for covering body inaccordance with Islamic syariah. Narrative semiotics can be understood as effort of recounting or rereada subject from overall text or message to view narrative or plot from signs in this case, it is advertisement.Advertisement basically is assumed as a narrative that tells certain meanings therefore advertisement iscreated also published through media in order to influence readers. In Greimasâ opinion, advertisementis considered as text that has actant that becomes model or subject organizing plot in a text as destinator/sender, receiver, subject, object and also adjuvant even traitor/resistor. By using Greimasian semiotic,this research reveals latent meaning inside Muslim fashion advertisement that shows Muslim fashionproduced by Muslim house especially ZeaTM Zenura brand basically not only just communicating Muslimfashion advertisement but also constructing myths that the fashion is Muslim fashion for family and verysuitable to wear in special events such as Muslim celebration day, Idul Fitri 1433 H